Syntactic complexity of online newspaper editorials across countries - Dwi Indarti (Studies in English Language and Education, 2018)
This study attempts to reveal the syntactic complexity of online English newspaper editorials across countries. The data was taken from ten online English newspaper and was analyzed by using L2 syntactic complexity analyzer (Lu, 2010). Second Language Syntactic Complexity Analyzer (L2SCA) program displays fourteen syntactic complexity measures. Those editorials were derived from ten online newspaper in the USA, UK, Egypt, Indonesia, Japan, Malaysia, Nigeria, Pakistan, Russia and Singapore. All the editorials were written in English by the local newspaper editors, so they contain varied production units and grammatical structures from native English writers and non-native English writers. The results of the study reveal that the non-native online newspaper, The Vaguardgnr from Nigeria, shows the most complexity of sentence structure as indicated in the length of production unit which correlate with higher levels of proficiency. Meanwhile, the native online newspaper, The New York Times from USA, displays the highest score of subordination, which indicate complexity at the beginning and intermediate levels of proficiency. Hence, in most newspapers, the purpose of editorials is to influence the opinions of readers on some controversial issues.